2022
DOI: 10.3390/ijms23020870
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Role of Microbiome in the Prevention of Urinary Tract Infections in Children

Abstract: The microbiome of the urinary tract plays a significant role in maintaining health through the impact on bladder homeostasis. Urobiome is of great importance in maintaining the urothelial integrity and preventing urinary tract infection (UTI), as well as promoting local immune function. Dysbiosis in this area has been linked to an increased risk of UTIs, nephrolithiasis, and dysfunction of the lower urinary tract. However, the number of studies in the pediatric population is limited, thus the characteristic of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 80 publications
(134 reference statements)
0
12
0
Order By: Relevance
“…In contrast, different immune variants can exacerbate acute and chronic infection or be protective [12,14]. Based on the current knowledge about the pathogenesis of rUTI, there are three main components involved: pathogen virulence, the host's defense mechanism, and the environment [15]. The etiology of UTI includes Gram-positive and Gram-negative bacteria and fungi, but UPEC accounts for a significant proportion of rUTI [6].…”
Section: Pathogenesis Of Rutimentioning
confidence: 99%
“…In contrast, different immune variants can exacerbate acute and chronic infection or be protective [12,14]. Based on the current knowledge about the pathogenesis of rUTI, there are three main components involved: pathogen virulence, the host's defense mechanism, and the environment [15]. The etiology of UTI includes Gram-positive and Gram-negative bacteria and fungi, but UPEC accounts for a significant proportion of rUTI [6].…”
Section: Pathogenesis Of Rutimentioning
confidence: 99%
“…Dysbiosis of the natural microbiota of the urinary tract is related to the development of infections. Under normal conditions, the genitourinary microbiota plays a protective role against urinary tract infections [ 24 ]. Lewis et al [ 25 ] showed that women with low levels of Lactobacillus are more commonly colonized with pathogens than those with diverse microbiota, which naturally decreases the risk of UTI development.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship of IM disorders, called dysbiosis, with certain disease development and an increase in human susceptibility to infections has also been determined. 1 - 8 The IM is the largest and crucial microbial community of the human body, which is regarded as a “regulator” of the microbiota of other body areas, and, presumably, as a source of origin of such local communities, including the microbial communities in the urinary tract, also called “urobiome.” 9 - 13 …”
Section: Introductionmentioning
confidence: 99%